We should pay more attention to the community context in the disaster management: lessons learned from the first days after the Khoy earthquake - Ehsan Rhikhtegar; Behrouz Fathi (Health Science Monitor, 2023)
Dear Editor-in-Chief On January 28, the city of Khoy (the northwest of Iran) was struck by a strong earthquake with a magnitude of 5.9 on the Richter scale at 21:44:44 and a depth of 7 km, X: 45.01 and Y: 38.05 (1). This earthquake occurred 117 kilometers from Urmia, the capital of the West Azerbaijan Province. Over 370,000 people were affected by this earthquake, which resulted in three deaths and more than 1,750 injuries. More than 70 villages in the area and the cities of Khoy and Firouraq were damaged to varying degrees (2). A few days before the earthquake, a rumor circulated on the internet that there would be a strong earthquake on Saturday January 29th, followed by a magnitude 9 earthquake on February 16th. After the earthquake, many of affected people left their homes in the early hours and went to the cities of Salmas, Urmia, and Tabriz. In the quake-hit area, people took shelter in makeshift camps or tents near the destroyed homes. Humanitarian aid arrived from all over the country and neighboring provinces to the affected area. Government organizations, military, religious bodies, associations, unions, and non-governmental organizations provided the basic needs and equipment needed by the people of the earthquake-affected area. However, the distribution of food and equipment among people affected by the earthquake was inappropriate. For instance, some donors were providing aid directly, essential drugs were not adequately supplied. Despite the large amount of aid sent, a distribution aid was concentrated in some areas and neglected in other areas, and some people did not yet manage to receive essential items such as food, blankets, tent heating equipment (3). In Urmia, adequate services were provided in the camps established in the mosques. Health teams had a daily presence in the mosques, providing free medical and health services. The mosques were run by the Basij (volunteer mobilization force), or Mosque Council, with most help coming from donors and official and unofficial communications from the council. One notable thing was that earthquake victims tended to receive more than actually need medical and pharmaceutical services, as well as other services. Some people were unwilling to leave their homes and settled in the makeshift camps for reasons such as fear of possible theft of their property from damaged houses. Due to rumors of a stronger earthquake on February 16th, those shelter in nearby cities did not want to return to the disaster area. Iran is located on the earthquake fault line (4), and several faults in the northwest of the country activated in the past and caused devastating earthquakes such as the earthquakes with a magnitude of 5.4 on the Richter scale that occurred in the cities of Khoy and Salmas in 1900 and 1930 (5,6). Therefore, the occurrence of similar or stronger earthquakes in this area can be expected in the region in future (6,7). In general, observations show that the scale of destruction and damage does not exceed national and even provincial capabilities. However, one thing that is evident, despite the formation of numerous crisis preparedness committees before the earthquake, the lack of complete coordination in the calculation, as well as supply and distribution of the real basic needs among stakeholders in the crisis management scene is one of the main challenges. Considering the occurrence of similar problems during similar natural disasters in the northwest region, it is suggested that policy makers focus more on the community context in disaster management. A model that can align the participation of government organizations, unions, and social groups can lead to more coordination in the proper distribution of aid and meeting the needs of the victims in the early days.